2013
DOI: 10.1080/17450128.2012.738948
|View full text |Cite
|
Sign up to set email alerts
|

Comparing psychiatric symptoms among children of substance-abusing parents with different treatment histories

Abstract: It appears that no studies to date have compared the psychiatric functioning of children of substance-abusing parents (COSs) across substance abuse treatment histories (e.g., inpatient, outpatient, residential). Different treatment histories may reflect differences in the severity of drug use, degree of impairment, or drug of choice, which may result in different symptomatology among COSs. Moreover, this information may be important for family-based treatment and prevention planning. In the current study, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…In our study, we found low father education, high family history of somatization, psychiatric and medical disease, high rates of marital problems and domestic violence as familial disadvantages, and our results supported that these stressful situations and poorer family functioning may be important risk factors for SSRD. Consistent with our results, it has been reported that somatization in parents, presence of chronic disease and psychopathology in the family, traumatic experiences in the family, and poor family functioning are among familial risk factors for somatization 9,14,[30][31][32][33] . Some theories explain the formation of somatization in children in the context of such familial risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found low father education, high family history of somatization, psychiatric and medical disease, high rates of marital problems and domestic violence as familial disadvantages, and our results supported that these stressful situations and poorer family functioning may be important risk factors for SSRD. Consistent with our results, it has been reported that somatization in parents, presence of chronic disease and psychopathology in the family, traumatic experiences in the family, and poor family functioning are among familial risk factors for somatization 9,14,[30][31][32][33] . Some theories explain the formation of somatization in children in the context of such familial risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…In line with Hosman and colleagues (2009) and findings from other studies (Hussong et al, 2008;Sayal et al, 2009;Burns et al, 2013) suggesting that the actual development of problematic behavior of the child often depends on the number and severity of detrimental characteristics at the child, parent, and/or environmental level, we expected to find more problems regarding the mental health of CSAP in families with lower levels of education of the parents, parental poly-drug use, unemployment, and financial problems.…”
supporting
confidence: 75%
“…Burstein, Stanger, Kamon, & Dumenci's (2006) study of 399 children of 251 parents during substance abuse treatment correlated Child Behavior Checklist (CBCL) scores to parenting practices and found that negative parenting (less positive involvement, negative or ineffective discipline, and less monitoring) was significantly correlatedwith externalizing behavior in this group of CSAP. Burns, Solis, Shadur, & Hussong (2013) investigated the psychiatric wellbeing of children (n = 81) whose parents were in different types of substance abuse treatment. According to their findings, children of parents in medication/detoxification treatment showed higher levels of somatization, social withdrawal, and attention problems compared to children whose parents received outpatient treatment.…”
mentioning
confidence: 99%
“…The psychiatric disorders among children with parental alcoholism had higher somatization scores, social withdrawal, greater attention problems,[ 22 ] depression, hyperactivity disorder, and substance use disorders. [ 23 24 ] The physical, psychological health, wellbeing, and quality of life are significantly impacted in families where the father is alcohol-dependent.…”
Section: Introductionmentioning
confidence: 99%